Analisis K-Means Clustering pada Sistem Presensi Mobile dengan Fitur GPS Radius dan Foto Selfie untuk Pegawai Non-PNS di Puskesmas Kosambi - Adih Adih; Wahyu Aji Dwi Pangestu; Muhamad Fauzi Akbar; Purnamasari Purnamasari; Saprudin Saprudin (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
Puskesmas Kosambi employs Non-PNS staff whose discipline, particularly regarding attendance and work location, needs to be evaluated. The previous manual attendance system was found to be ineffective in monitoring staff discipline. This study aims to develop a mobile-based attendance system equipped with GPS radius and selfie photo features to improve the accuracy and management of attendance. The GPS radius feature ensures that staff can only clock in within the designated area, such as the Puskesmas area, while the selfie photo feature verifies the identity of the staff member clocking in. This study involved 24 Non-PNS staff members and used the K-Means Clustering algorithm to group staff based on their discipline levels. The results showed that the system was effective in improving staff discipline, with 11 employees categorized as highly disciplined, 10 as moderately disciplined, and 3 as lowly disciplined. The implications of this study suggest that the implementation of a mobile-based attendance system can improve attendance monitoring and enhance work discipline at Puskesmas Kosambi.